DINAMIKA ORGANISASI KEMASYARAKATAN DAN REFORMASI KEBIJAKAN PEMERINTAHAN YANG DEMOKRATIF - Irfan Setiawan; Melianus Mesakh Taebenu (Jurnal Politik Pemerintahan Dharma Praja, 2025)
This study aims to examine the dynamics of governance related to community organizations and their impact on democracy more comprehensively in Indonesia. This study uses a qualitative approach with a descriptive-analytical design. Data in this study are sourced from literature studies, document analysis, and comparative studies. Legal documents are used as primary sources, including Law Number 17 of 2013 and Law Number 16 of 2017, as well as various Joint Ministerial Decrees used by the government as the basis for disbanding mass organizations. This study shows that the development of mass organizations in Indonesia after the Reformation has shifted from the spirit of liberalization that emphasizes civil liberties to a pattern of stricter state control. The impact of this policy is evident in the declining quality of Indonesian democracy as indicated by the Democracy Index (EIU) score and the Freedom House report. The novelty of this study lies in combining legal-political analysis of government policies regarding mass organizations with their implications for economic development. This study offers a perspective on policy reform based on hybrid governance while encouraging state-civil society collaboration towards a more substantive and inclusive democratic consolidation.